Kaposi Sarcoma among HIV Infected Patients in Lagos University Teaching Hospital, Nigeria: A 14-Year Retrospective Clinicopathological Study. (13th March 2016) - Akinde, Olakanmi; Obadofin, Omobolade; Adeyemo, Titilope; Omoseebi, Oladipo; Ikeri, Nzechukwu; Okonkwo, Ikechukwu; Afolayan, Olatunji
Abstract : Background. Despite the increased incidence of Kaposi sarcoma (KS) resulting from the Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) pandemic, there is still significant underreporting of KS in this environment. Objectives. This study was aimed at determining the incidence and clinicopathologic patterns of KS among HIV infected patients in Lagos University Teaching Hospital (LUTH), Nigeria, over a 14-year period: January 2000 to December 2013. Methodology. The materials for this study included patients' hospital clinical files, duplicate copies of histopathologic reports, and tissue blocks and corresponding archival slides in the Anatomic and Molecular Pathology Department and the HIV/AIDS unit of the Department of Haematology. Results. Within the study period, 182 cases of KS were diagnosed, accounting for 1.2% of all patients managed for HIV/AIDS and 2.99% of solid malignant tumours. The male-to-female ratio and modal age group were 1 : 1.3 and 5th decade, respectively. Most cases (90%) had purely mucocutaneous involvement with the lower limb being the commonest site (65.8%). The majority of lesions were plaques (65.8%). Vascular formation was the predominant histologic type seen (43.5%). Conclusion. KS in Lagos followed the same epidemiologic trend as other centers in Nigeria, with an increasing incidence in this era of HIV/AIDS.